2003
DOI: 10.1002/ajmg.b.20050
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transmission of novel polymorphisms in the somatostatin receptor 5 (SSTR5) gene in patients with autism

Abstract: Infantile autism is a pervasive developmental disorder with a strong genetic component. The mode of inheritance appears to be complex and no specific susceptibility genes have yet been identified. Chromosome 16p13.3 may contain a susceptibility gene based on findings from genome scans and reports of chromosome abnormalities in individuals with autism. The somatostatin receptor 5 (SSTR5) gene is located on chromosome 16p13.3 and is thus a positional candidate gene for autism. SSTR5 may also be a functional cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…These data represent one of the more significant association between a candidate gene and ASD in the publicly available AGRE data set (www.agre.org). [52][53][54][55][56][57][58][59][60][61] The triad data also define a minimal population for future family-based association studies that is both a powerful and cost-efficient alternative to using extended nuclear families.…”
Section: Discussionmentioning
confidence: 99%
“…These data represent one of the more significant association between a candidate gene and ASD in the publicly available AGRE data set (www.agre.org). [52][53][54][55][56][57][58][59][60][61] The triad data also define a minimal population for future family-based association studies that is both a powerful and cost-efficient alternative to using extended nuclear families.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the rs34037914 and rs642249 were not genotyped in a study performed Filopanty et al . (16) The C allele of the rs169068 was associated with the presence of bipolar affective disorder in a British but not in a Danish population (24), while there was a lack of association with autism in both Danish and French populations (25). No association was found between this SNP and risk or survival of pancreatic cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…A primate-specific single nucleotide polymorphism (SNP) in the human somatostatin gene [C/T polymorphism (rs4988514)] is associated with increased risk in Alzheimer’s disease progression and additive effect with the APOE epsilon4 allele(Vepsalainen et al, 2007; Xue et al, 2009), although this was not confirmed in larger genome-wide association studies (GWAS) (Hollingworth et al, 2011; Guerreiro et al, 2013). Leu48Met and Pro335Leu SNPs in the SST5 gene are of potential significance to patients with bipolar disorder (Nyegaard et al, 2002), but no associations of SST5 SNPs are found in patients with autism (Lauritsen et al, 2003). The paucity of associations with somatostatin gene variants is surprising and may reflect either strong negative selection against genetic variations in this gene, or alternatively, dilution of signal due to heterogeneity of DSM-IV-based cohorts in genetic association studies.…”
Section: Somatostatin: Genes Neurons and Pharmacologymentioning
confidence: 99%